Measurement of the Cross Section for Electroweak Production of Zγ in Association With Two Jets and Constraints on Anomalous Quartic Gauge Couplings in Proton–proton Collisions at S=8 Tev - Khachatryan, V.; Karapınar, Güler; Sirunyan, A.M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Piedra Gomez, J. (Elsevier B.V., 2017)
A measurement is presented of the cross section for the electroweak production of a Z boson and a photon in association with two jets in proton–proton collisions at s=8 TeV. The Z bosons are identified through their decays to electron or muon pairs. The measurement is based on data collected with the CMS detector corresponding to an integrated luminosity of 19.7 fb−1. The electroweak contribution has a significance of 3.0 standard deviations, and the measured fiducial cross section is 1.86−0.75 +0.90(stat)−0.26 +0.34(syst)±0.05(lumi) fb, while the summed electroweak and quantum chromodynamic total cross section in the same region is observed to be 5.94−1.35 +1.53(stat)−0.37 +0.43(syst)±0.13(lumi) fb. Both measurements are consistent with the leading-order standard model predictions. Limits on anomalous quartic gauge couplings are set based on the Zγ mass distribution. © 2017 The Author
Keywords: Aqgc; Cms; Electroweak Production; Physics